Family maintenance (nafkah): a study on awareness of maintenance issues among university students / Atiratun Nabilah Jamil, Nurhidayah Muhamad Sharifuddin and Khafizatunnisa’ Jaapar - Jamil, Atiratun Nabilah; Sharifuddin, Nurhidayah Muhamad; Jaapar, Khafizatunnisa’ (Center for Islamic Philantrophy & Social Finance (CIPSF), 2023)
This study aims to assess the level of awareness among students taking the Islamic Family Institution Management course (HKR111) regarding the obligations and issues related to family maintenance. The research methodology involves a survey to evaluate students' knowledge of maintenance obligations and their perspectives on this responsibility. The findings indicate that awareness of maintenance obligations has not yet reached an optimal level, with most having only a basic understanding of the concept of family maintenance. Factors such as education, religion, and residential area play a crucial role in shaping their perceptions on this matter. Students with higher formal education and upbringing in religious values tend to have a deeper understanding of maintenance obligations. Media influence also impacts their perception of maintenance responsibilities. Media content that tends to portray this responsibility negatively or superficially can influence students' attitudes towards the concept of family maintenance. Therefore, there is a need to enhance students' awareness through formal education and religious instruction, as well as promote the creation of media content that provides a balanced and realistic view of maintenance responsibilities. Overall, this study suggests that there is room for improving the general public's awareness of family maintenance. Ongoing efforts are necessary to ensure they understand the significance of this responsibility in shaping a responsible and ethical society.